Germline PTEN mutations are rare and highly penetrant - Rustad Cecilie F (Hereditary Cancer in Clinical Practice, 2006)
Abstract Cowden syndrome (multiple hamartoma syndrome, MIM 158350) is an early onset syndrome characterized by multiple hamartomas in the skin, mucous membranes, breast, thyroid and endometrium. Patients with Cowden syndrome have increased risk of breast cancer, thyroid cancer and endometrial cancer. In 1997 germline mutations in PTEN were demonstrated to cause Cowden syndrome. We report the results of diagnostic and predictive testing in all families with Cowden syndrome or suspected Cowden syndrome registered at the Norwegian cancer family clinics. PTEN mutations were found in all six families meeting the clinical criteria for Cowden syndrome, in none of the two families assumed to have Cowden syndrome but not fulfilling the criteria, and in none of the eight families selected in our computerized medical files to have a combination of breast and thyroid cancers. Age-related penetrances for the various neoplasms are given. All families but one were small and de novo mutations were found.